Active and Passive Plasmonic Devices for Optical Communications - Melikyan, Argishti (Karlsruhe Series in Photonics and Communications / Karlsruhe Institute of Technology, Institute of Photonics and Quantum Electronics (IPQ), 2018)
A short introduction to the theory of surface plasmon polaritons (SPPs) is given. The application of the SPPs in on-chip signal processing is discussed. In particular, two concepts of plasmonic modulators are reported, wherein the SPPs are modulated by 40 Gbit/s electrical signals. Phase and Mach-Zehnder modulators employing the Pockels effect in electro-optic organic materials are discussed. A few micro-meter long SPP absorption modulator based on a thin layer of indium-tin-oxide is reported.